The Principal's Role in the Implementation of the KMA Curriculum No. 183 and No. 184 of 2019 - Muhamad Khoirur Roziqin; Danna Istiqomah (SCHOOLAR: Social and Literature Study in Education, 2021)
This Final Project discusses the role of the principal in implementing the KMA curriculum Number 183 and Number 184 of 2019 at Madrasah Aliyah Al Ihsan Kalikejambon Tembelang Jombang. This madrasah has implemented the KMA No. 183 and No. 184 of 2019. The purpose of the researcher is to find out how the role of the principal in implementing the KMA No. curriculum. 183 and No.184 of 2019, supporters and obstacles in implementing the KMA curriculum No. 183 and No. 184 of 2019. The stages in implementing the KMA No. curriculum. 183 and No. 184 of 2019 starting from the presence of researchers to the location directly looking for data sources, interviews, observation and documentation as data collection steps then analyzing data to find out how far the implementation process is in the learning process of Islamic education in the application of the KMA No. 183 and No. 184 of 2019 at Madrasah Aliyah Al Ihsan Kalikejambon Tembelang Jombang. Based on the results of research, Madrasah Aliyah Al Ihsan Kalikejambon Tembelang Jombang has implemented the KMA curriculum No. 183 and No. 184 in 2019. Various facilities and policies are also implemented as a form of the principal's efforts to support the implementation of this curriculum. There are no obstacles in the implementation of this curriculum because the KMA curriculum No.183 and No.184 of 2019 is a refinement curriculum from the previous curriculum, but there are also obstacles in its implementation due to circumstances that cannot be forced in the delivery of material directly